2020
DOI: 10.1002/marc.201900437
|View full text |Cite
|
Sign up to set email alerts
|

Challenges to the Stability of Active Layer Materials in Organic Solar Cells

Abstract: In the past 20 years, organic solar cells (OSCs) have made great progress in pursuing high power‐conversion efficiencies, reaching the application threshold. Instead, device stability is becoming particularly important toward commercialization. There are many factors influencing the stability of OSCs, such as light, heat, humidity, oxygen, as well as device structure. Active layer materials, as the most critical functional layer in the devices, are greatly affected by these factors in terms of both efficiency … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
43
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(45 citation statements)
references
References 221 publications
(153 reference statements)
0
43
0
Order By: Relevance
“…The decrease in current density is more severe in the case of PEDOT: PSS-based devices with a final value around 30% of the original one ( Figure S6b in Supplementary Materials ). On the other hand, the use of CuCrO 2 as HTL leads to the conservation of a J sc around 60% of the initial value after 2 h. The loss in short circuit current found for both the devices is attributed to the chemical degradation or morphological evolution of the AL, with many factors contributing to the deterioration of this material [ 64 , 65 ]. These photoactive polymers undergo a phase separation phenomena, leading to a vertical gradient of the acceptor and donor material, significantly impacting the photogeneration process, charge transport, and carrier recombination [ 66 ], thus, jeopardizing the short-circuit current.…”
Section: Resultsmentioning
confidence: 99%
“…The decrease in current density is more severe in the case of PEDOT: PSS-based devices with a final value around 30% of the original one ( Figure S6b in Supplementary Materials ). On the other hand, the use of CuCrO 2 as HTL leads to the conservation of a J sc around 60% of the initial value after 2 h. The loss in short circuit current found for both the devices is attributed to the chemical degradation or morphological evolution of the AL, with many factors contributing to the deterioration of this material [ 64 , 65 ]. These photoactive polymers undergo a phase separation phenomena, leading to a vertical gradient of the acceptor and donor material, significantly impacting the photogeneration process, charge transport, and carrier recombination [ 66 ], thus, jeopardizing the short-circuit current.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, the thermal stability of OSCs is important due to the microstructure of active layer concerned with performance is very sensitive to temperature. [45] The thermal stability curves of BHJ and PPHJ structure ternary films measured at 150 °C are shown in Figure 3d, and relevant parameters are listed in Tables S2 and S3, Supporting Information. It can be observed that the PM6/10%ICBA:IT-4F system with PPHJ structure exhibits better thermal stability as compared with the traditional BHJ structure.…”
Section: Resultsmentioning
confidence: 99%
“…Solar cells work under various operational stresses such as solar illumination, increased temperature, and exposure to air. 102,[257][258][259][260][261][262] Intrinsic degradation mechanisms of the active layer in OSCs include degradation in dark caused by the morphological changes (rearrangement of donor and acceptor domains) that occur over time and photo-chemical reactions of the organic semiconductor materials in the presence of illumination. [263][264][265][266][267] In terms of morphological stability, all-polymer solar cells have attracted much attention since a polymer donor and a polymer acceptor can be entangled to form a much more metastable blend, leading to superior thermal and mechanical stabilities compared to small moleculebased OSCs.…”
Section: Discussionmentioning
confidence: 99%